2008
DOI: 10.1007/s10336-008-0322-x
|View full text |Cite
|
Sign up to set email alerts
|

Brood-guarding behaviour in Cory’s Shearwaters Calonectris diomedea

Abstract: Brood-guarding (or the continual attendance at the nest by one parent) has been relatively little studied in altricial birds. Parental investment in brood-guarding is often highly variable within a species, and the study of such variability may contribute to the understanding of the functions and regulation of this behaviour and of the tradeoffs involved in the choice between attending the nest and leaving to forage. In some colonial birds, it has been found that early nesting pairs attend their chick for long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 15 publications
2
16
0
Order By: Relevance
“…At SG, shearwaters performed much longer trips, reaching in most cases the Western African shelf, also an important upwelling zone (Davenport et al 2002). This last result indicates that the food availability around SG may be scarce, which agrees with previous studies that reported lower feeding frequencies (Granadeiro et al 1998b) and longer foraging trips at this colony (Catry et al 2009;Paiva et al 2010b), when compared to BE. Indeed, the length of foraging trips is known to be largely influenced by the local food availability (Uttley et al 1994) and by the distance to the most profitable areas (Paiva et al 2010c).…”
Section: Foraging Strategy and Chick Conditionsupporting
confidence: 90%
See 1 more Smart Citation
“…At SG, shearwaters performed much longer trips, reaching in most cases the Western African shelf, also an important upwelling zone (Davenport et al 2002). This last result indicates that the food availability around SG may be scarce, which agrees with previous studies that reported lower feeding frequencies (Granadeiro et al 1998b) and longer foraging trips at this colony (Catry et al 2009;Paiva et al 2010b), when compared to BE. Indeed, the length of foraging trips is known to be largely influenced by the local food availability (Uttley et al 1994) and by the distance to the most profitable areas (Paiva et al 2010c).…”
Section: Foraging Strategy and Chick Conditionsupporting
confidence: 90%
“…Mixed-effects ANOVAs were used to test for differences in d 13 C and d 15 N between adults and their offspring, between colonies and the interaction between both, with nest used as a random factor. Although the hatching dates of Selvagem Grande and Berlenga are generally similar (Catry et al 2009), the age of our sampled chicks was unknown, and we considered that wing and tarsus length should give us a reasonable indication of chick age at both colonies (Granadeiro 1991). An analysis of covariance (ANCOVA) was used to test for differences in chick weight between the colonies, using wing length as a covariate.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals nesting on Selvagem Grande generally make much longer foraging trips than birds nesting on Berlenga (Granadeiro et al 1998;Catry et al 2008). This is presumably a result of the lower productivity of the ocean in pelagic waters and, possibly, because of increased intraspecific competition in pelagic waters in comparison to waters over the continental shelf, where birds face less competition and the smaller colony may be limited by nesting site rather than food availability.…”
Section: Moult Progress Differed Between Populationsmentioning
confidence: 99%
“…This is presumably a result of the lower productivity of the ocean in pelagic waters and, possibly, because of increased intraspecific competition in pelagic waters in comparison to waters over the continental shelf, where birds face less competition and the smaller colony may be limited by nesting site rather than food availability. In fact, birds on Selvagem not only make longer foraging trips during incubation (Catry et al 2008), but also they can engage in a dual strategy of mixed short and long foraging trips during chick rearing (Granadeiro et al 1998). These activities are indicative of a shortage of resources in the vicinity of the colony (Chaurand and Weimerskirch 1994;Weimerskirch et al 1997).…”
Section: Moult Progress Differed Between Populationsmentioning
confidence: 99%
See 1 more Smart Citation